Students’ metacognitive skill in mathematics learning with cabri geometry II plus - Rahmah Johar; . Khalisna; Taufik Fuadi Abidin (Proceedings of The Annual International Conference, Syiah Kuala University - Life Sciences & Engineering Chapter, 2013)
Metacognitive skill is the awareness of one's thinking about the thinkingprocess itself, whereas consciousness is the awareness of one's thinking about what to do. The subjects for this research were five students from class VII-1 SMP 1 Banda Aceh. Research data collection used the sheet metacognitive questions. Data were analyzed descriptively to interpret students' metacognitive skills in learning how to use Cabri Geometry II Plus software. The results showed that the metacognitive abilities of students increased from the first meeting to the fourth meeting